Pengaruh motivasi dan disiplin kerja terhadap kinerja karyawan pada PT. Kreativa Surya Pratama Bandung - Muhammad Rizan Nur Samsi; Tiris Sudrartono (Jurnal Kajian Manajemen dan Wirausaha, 2021)
This research aims to identify the effect of motivation and work discipline on employee performance at PT Kreativa Surya Pratama Bandung. The type of research that was tried was listed as the type of research quantitatively. In collecting information, it was tried by distributing questionnaires with a sample of 70 respondents taken from a total population of 237 people using the Slovin equation. The calculation process used in this research uses SPSS v26. The method of analyzing information uses multiple linear regression. The results of this research prove partially or t-test and simultaneously or F-test motivation and work discipline affect employee performance by proving a significant value. As well as the results of the coefficient of determination obtained at the adjusted R square value of 0.920. Which means that motivation and work discipline affect employee performance by reaching a value of 92% with the remaining 8% explained by other variables not examined in this research.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//